Evaluation Tool for Traditional Chinese Medicine Students in China: A Competency Perspective. (July 2019) - Zheng, Boyang; Sun, Guiping; Wang, Hourong
Traditional Chinese medicine (TCM) is an important component of China's medical system. How to educate TCM practitioners in China, therefore, has become a crucial issue. To contribute to this issue, the current research identified the competency model of TCM practitioners in China and developed an evaluation for TCM students. We combined Bloom's taxonomy with our model construction to examine the current TCM practitioners' requirements. Following the protocol of developing a measurement, we interviewed 20 TCM practitioners, conducted two rounds of surveys in China ( n = 220/ n = 489), ran exploratory factor analysis (EFA) and confirmatory factor analysis (CFA), and examined the correlation between the measurement and self-rated outcomes. The evaluation tool of TCM students consists of five factors: modern medical knowledge and skills, TCM medical knowledge and skills, professional ethics, communication and cooperation skills, and clinical practices . The reliability and validity of our evaluation tool were testified. Our work may contribute to TCM education in China.